Characterization of dimethylsulfoxide/glycerol mixtures: a binary solvent system for the study of "friction-dependent" chemical reactivity. Issue 27 (24th June 2016) - Angulo, Gonzalo; Brucka, Marta; Gerecke, Mario; Grampp, Günter; Jeannerat, Damien; Milkiewicz, Jadwiga; Mitrev, Yavor; Radzewicz, Czesław; Rosspeintner, Arnulf; Vauthey, Eric; Wnuk, Paweł
Abstract : The properties of binary mixtures of dimethylsulfoxide and glycerol, measured using several techniques, are reported. Abstract : The properties of binary mixtures of dimethylsulfoxide and glycerol, measured using several techniques, are reported. Special attention is given to those properties contributing or affecting chemical reactions. In this respect the investigated mixture behaves as a relatively simple solvent and it is especially well suited for studies on the influence of viscosity on chemical reactivity. This is due to the relative invariance of the dielectric properties of the mixture. However, special caution must be taken with specific solvation, as the hydrogen-bonding properties of the solvent change with the molar fraction of glycerol.